Differences in agility and explosive power of basketball players in relation to their positions on the team - Mitic, M.; Paunovic, M.; Živkovic, M.; Stojanovic, N.; Bojic, I.; Kocic, M. (Facta Universitatis: Series Physical Education and Sport, 2018)
Basketball is a sports game which consists of rapid changes in direction of movement, sudden stopping and starting for driving and dribbling and a great number of jumps. The various positions on a basketball team precisely determine the requirements for specific forms of movement, even though contemporary basketball strives for all players in all positions to possess the aforementioned abilities. A sample of 15 male basketball players, divided into three groups of five players each, based on their positions on the team, including the guard, forward and center position, was used to determine differences in agility (Agility T Test, Hexagon Agility Test, Illinois Agility Test, Lane Agility Drill) and explosive power (the Squat jump, Countermovement Jump, Drop Jump and One-legged Counter Movement Jump). To determine the differences between the basketball players in relation to their positions on the team, the ANOVA analysis for independent samples was used as was a post-hoc analysis. The research results have indicated that there is a difference between the guard position compared to the forward and center position.